Health Education for Adolescent Girls in Overcoming Dismenorhea without Medication - Mayasari Putri Ardela; Anis Nikmatul Nikmah; Nara Lintan Mega Puspita; Meirna Eka Fitriasnani; Rahma Kusuma Dewi; Alfika Awatiszahro; Khofidhotur Rofi’ah; Siti Aminah (Journal of Community Engagement in Health, 2024)
Dysmenorrhea is pain in the lower abdomen during menstruation which is generally caused by contractions of the myometrium due to prostaglandin production. In Indonesia, 43-93% girls experiencing dysmenorrhea. When experiencing unbearable menstrual pain, many women need medication to relieve it. However, the use of drugs often has side effects on the body. One of the non-pharmacological management methods that can be used is relaxation techniques that inhibit the brain from producing pain sensations and do not cause side effects for the body. The purpose of the community service activities carried out at Senior High School 1 Kandat, Kediri Regency is to provide education about non-pharmacological therapy methods in reducing the intensity of dysmenorrhea pain that are easy to apply, especially to adolescent girls when experiencing menstrual pain. The population of this community service is female students. The implementation of this community service activity is by providing health education on how to overcome menstrual pain without medication. The result of this activity was an increase in the level of knowledge of 85% of female students on how to overcome menstrual pain without medication. This activity concludes that it was implemented and resulted in changes by the target output, namely knowledge on overcoming menstrual pain without medication. It is hoped that the counseling provided can be implemented routinely and applied.